2002
DOI: 10.1210/jc.2002-020298
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Reduces Postprandial Accumulation and Cholesteryl Ester Transfer Protein-Mediated Remodeling of Triglyceride-Rich Lipoprotein Subspecies in Type IIB Hyperlipidemia

Abstract: The effect of atorvastatin, at 10 mg or 40 mg for 6 wk, on lipid and lipoprotein metabolism during the postprandial phase in subjects (n = 11) displaying type IIB hyperlipidemia was evaluated. The postprandial increment in area under the curve above baseline concentrations in type IIB subjects was significantly decreased by atorvastatin for plasma triglyceride (A10: -42% and A40: -55%, P < 0.01), chylomicrons (CMs) (A10: -24% and A40: -40%, P < 0.03) and VLDL-1 (A10: -54% and A40: -52%, P < 0.02). Before atorv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
(11 reference statements)
1
27
0
Order By: Relevance
“…The atorvastatin subjects on placebo also had substantially lower serum concentrations of lathosterol (reduced cholesterol synthesis) and, in turn, decreased fecal sterol content (16, see supplementary data), parameters associated with chylomicron production. Moreover, atorvastatin therapy in hyperlipidemic men has been shown to stimulate intestinal mRNA expression of the LDL receptor and Niemann-Pick C1Like 1 and to decrease mRNA levels dysbetalipoproteinemia ( 38,39 ), and CHD ( 40,41 ). The reductions have been associated with enhanced clearance of apoB-48 ( 22 ) and chylomicron-like emulsions ( 42 ) in subjects with dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…The atorvastatin subjects on placebo also had substantially lower serum concentrations of lathosterol (reduced cholesterol synthesis) and, in turn, decreased fecal sterol content (16, see supplementary data), parameters associated with chylomicron production. Moreover, atorvastatin therapy in hyperlipidemic men has been shown to stimulate intestinal mRNA expression of the LDL receptor and Niemann-Pick C1Like 1 and to decrease mRNA levels dysbetalipoproteinemia ( 38,39 ), and CHD ( 40,41 ). The reductions have been associated with enhanced clearance of apoB-48 ( 22 ) and chylomicron-like emulsions ( 42 ) in subjects with dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Although initial studies (30)(31)(32)(33)(34)(35) evaluating the effect of statins on postprandial lipoprotein metabolism have shown conflicting results, recent studies using atorvastatin have uniformly shown positive effects on postprandial lipoprotein metabolism (13)(14)(15)(16)(17)(18). In patients with mild hypertriglyceridemia (plasma triglyceride concentration 2.4 Ϯ 0.9 mmol/l), pravastatin did not affect postprandial lipoprotein metabolism determined from a single triglyceride concentration measured 8 h after a standardized meal (32).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with coronary heart disease, Schaefer and colleagues showed that atorvastatin (40 mg/day), which almost normalized fasting triglycerides, also normalized remnant-like particle concentration following a standardized meal (17). In patients with combined hyperlipidemia, it was shown that atorvastatin causes reductions of postprandial plasma concentrations of all TRLs (15,16,18). In one study, atorvastatin therapy reduced cholesterol ester transfer from HDL to TRL, a pathway that is enhanced in untreated combined hyperlipidemia (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that CETP mediates the transfer of CE from HDL particles to LDL and VLDL particles in exchange for TG, and that this reciprocal neutral lipid transfer approaches equilibrium under physiological conditions. However, under conditions of increased VLDL levels as observed at 1 and 24 h after administration of rHDL to E3L mice, the increase in VLDL results in elevated acceptor activity for CETP, which would result in an increased net rate of TG transfer from VLDL particles to both HDL and LDL particles ( 27 ). Both TG-enriched HDL and LDL particles are avidly bound to hepatic lipase (HL) that effectively hydrolyzes TG (as well as phospholipid) to form small, dense LDL and HDL, respectively ( 28 ), thereby effectively eliminating TG from plasma.…”
Section: E3lmentioning
confidence: 99%